Expression changes and roles of Sema3A and Nrp1 in cultured rat cortical neurons after oxygen glucose deprivation - He, Ya; Yang, Ying; Wang, Ruili; Wang, Hui; Ma, Qiaoya; Chen, Songsheng; Shi, Daiying (Cellular and Molecular Biology, 2018)
To investigate the expression changes and roles of Semaphorin3A (Sema3A) and Neuropilin-1 (Nrp1) in cultured rat cortical neurons after oxygen glucose deprivation (OGD). Cultured cortical neurons of newborn SD rats were divided randomly into control group and OGD treatment group. Western blot was performed to detect the expression of Sema3A and Nrp-1 protein and TUNEL was used to detect apoptosis. With the increase of OGD treatment time, the cells become swollen, the axon disintegrated and death cells increased. After 2 hours of OGD treatment, the expression levels of Sema3A and Nrp1 were increased by 6.86 and 5.92 times of normal control, respectively. After transfection of Sema3A, apoptosis was significantly reduced with OGD treatment for 2 hours. OGD treatment could induce the up-regulation of Sema3A and Nrp1 expression and transfection of Sema3A could reduce apoptosis after OGD treatment. The results suggest that Sema3A plays a protective role for the neuron cell in OGD treatment.